REINFORCING VOCABULARY FOR ADULT LEARNERS: STRATEGIES FOR SUCCESS UZBEKISTAN STATE WORLD LANGUAGES UNIVERSITY - Normo'minova Zebiniso Kamol qizi; G‘.Raxmonov (PEDAGOGS, 2024)
Abstract: This article explores effective strategies for vocabulary reinforcement in adult learners. It examines the importance of active engagement, spaced repetition, and diverse learning methods. The article emphasizes the role of context, application, and personalized learning approaches in fostering long-term vocabulary retention.